An Evaluation of a Mental Health Promotion Programme to Improve Emotional, Social and Coping Skills in Children and Young People Attending Special Schools - Unwin, Gemma L.; Stenfert Kroese, Biza; Blumson, Jessica (Frontiers in Education, 2018)
1. Abstract Background Research evidence suggests that a child’s emotional, social and psychological wellbeing influences their future health, education and social prospects, and that positive, well-developed coping skills and high emotional literacy lead to improved self-esteem, reduced stress and reduced incidence of serious emotional problems in later life. Children with special educational needs and disabilities (SEND) are at a disadvantage as they tend to have lower levels of emotional literacy and may have limited opportunities or capacity to develop coping skills. Few targeted, evidence-based programmes aimed at improving emotional literacy and coping skills are currently available for use in SEND schools. Aims To evaluate the effectiveness, acceptability and feasibility of the school-based mental health promotion programme Zippy’s Friends in SEND schools. The study concentrated on the first three modules of the programme, implemented over the course of an academic year in a cohort of children and young people with SEND. Methods Fifty-three children and young people attending eight SEND schools participated in the educational programme and study. Quantitative and qualitative data were collected using standardised assessment scales, purposed-designed questionnaires, emotion recognition tasks and interviews to assess typical and maximal behaviour of the children as well feedback on the programme. Data were collected from children, parents/guardians/care givers, and teachers before and after the intervention. The results of the qualitative data will be presented elsewhere. Results Teachers’ ratings indicated that the children’s and young people’s social skills, emotional literacy, and emotional recognition improved over the course of the study. Significant improvements were observed in teachers’ ratings of communication, cooperation, assertion, responsibility and self-awareness. Parental ratings did not change over time. Conclusions This small-scale study indicates that the Zippy’s Friends programme is feasible and may lead to improved emotional literacy. However, further research is needed that uses a comparison group to isolate the effects of the programme from factors such as age-related maturation, development and usual school-based learning.